2019
DOI: 10.4038/jrrisl.v99i0.1888
|View full text |Cite
|
Sign up to set email alerts
|

Field screening of RRISL recommended rubber clones against Corynespora Leaf Fall Disease

Abstract: Identification of resistant clones is of vital importance in the management of Corynespora leaf fall disease (CLFD) of rubber. The recommended and potential clones were screened in a bud wood nursery which was especially designed for screening purposes at Ratnapura, Kalutara, Moneragala and Padiyatalawa. The lesion types agreed with the symptoms observed in the field plants and new symptoms have been identified from Padiyatalawa, in non-traditional rubber growing areas. Analysis of results from test methods sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Screening of available sources for resistance is the pre‐requisite to identify the genes responsible for resistance and incorporate them into the desirable clone. Several screening studies using clones from different countries have been reported (Atan et al., 2011; Chee, 1988; Fernando, Jayasinghe, Wijesundera, Silva et al., 2010; Fernando et al., 2019; Manju et al., 2001, 2010; Mushrif et al., 2020; Nghia et al., 2008; Shuib et al., 2015). However, there is much dissimilarity among the reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Screening of available sources for resistance is the pre‐requisite to identify the genes responsible for resistance and incorporate them into the desirable clone. Several screening studies using clones from different countries have been reported (Atan et al., 2011; Chee, 1988; Fernando, Jayasinghe, Wijesundera, Silva et al., 2010; Fernando et al., 2019; Manju et al., 2001, 2010; Mushrif et al., 2020; Nghia et al., 2008; Shuib et al., 2015). However, there is much dissimilarity among the reports.…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, the physiological response of each clone to different races of the pathogen as well as its genetic mechanism has to be elucidated. Several screening studies have been reported and the clones have been classified based on the severity (Atan et al., 2011; Chee, 1988; Fernando et al., 2019; Fernando, Jayasinghe, Wijesundera, Silva et al., 2010; Manju et al., 2001, 2010; Mushrif et al., 2020; Nghia et al., 2008; Shuib et al., 2015). These screening studies have been limited to laboratory studies like detached leaf assay or observation of nursery plants and field‐grown trees exposed to natural infection.…”
Section: Introductionmentioning
confidence: 99%
“…Ishani et al (2019) emphasized the potential of poverty alleviation through enhancements in technical efficiency within the smallholder rubber sector in the Kegalle district. Focusing on leaf fall disease, Fernando et al (2019) conducted an extensive investigation in a rubber plantation located in Padiyathalawa. Nakandala et al (2019) shed light on the correlation between water stress and the quality of immature rubber production in the Kilinochchi district.…”
Section: Justifications For the Selection Of Research Areamentioning
confidence: 99%
“…After several days, the petioles drop. The disease causes secondary leaf fall of young leaves that appear after wintering (Fernando, 1971). This causes a major defoliation leading to severe retardation of growth and extensive loss in yield up to 45% (Liyanage et al, 2016).…”
Section: Symptomsmentioning
confidence: 99%
“…A temperature of slightly below 30°C was best for production of O. heveae spores (Liyanage et al, 1986). Contrarily, the release and dispersion of spore were reported to be more favourable at high temperature together with the occurrence of great air turbulence (Fernando, 1971) and low moisture (Peries, 1966a). The outbreak is notably severe in subtropical regions (Liyanage et al, 2016).…”
Section: Epidemiologymentioning
confidence: 99%